Evaluating the impact of biochar amendment on antibiotic resistance genes and microbiome dynamics in soil, rhizosphere, and endosphere at field scale - Zhou, Zhenchao; Cui, Erping; Abid, Abbas Ali; Zhu, Lin; Xu, Jianming; Chen, Hong (Journal of hazardous materials, 2024)
Biochar amendment is a promising strategy for mitigating antibiotic resistance genes (ARGs) in soil and plants, but its effects on ARGs at field scale are not fully understood. Here, field trials were executed utilizing two plant varieties, Brassica juncea and Lolium multiflorum, with four types of biochar to investigate changes in ARGs and microbiome in soil, rhizosphere, root endophytes, and leaf endophytes. Results showed that biochar altered ARG distribution in soil and plant, and restrained their transmission from soil and rhizosphere to endophytes. A reduction of 1.2–2.2 orders of magnitude in the quantity of ARGs was observed in root and leaf endophytes following biochar addition, while no significant changes were observed in soil and rhizosphere samples. Procrustes and network analyses revealed significant correlations between microbial communities and mobile genetic elements with ARGs (P < 0.05). Besides, redundancy and variation partitioning analysis indicated that bacterial communities may play a dominant role in shaping the ARGs profile, contributing to 43 % of the variation observed in ARGs. These field results suggest that biochar amendment alone may not fully alleviate ARGs in soil, but it has a significant beneficial impact on food safety and human health by effectively reducing ARGs in plant endophytes. [Display omitted] •Biochar restrained ARGs transmission from the soil and rhizosphere to endophytes.•Biochar amendments reduced 1.2-2.2 orders of magnitude in ARGs in endophytes.•Bacterial communities could play a dominant role in shaping the ARGs profile.